Synthesis and Electronic Characterization of Weyl Semimetal TaSb2 Polycrystalline Material. Issue 9 (21st May 2022) - Masuda, Izumi; Miyazaki, Hidetoshi; Yoshimura, Masato; Ishii, Hirofumi; Nishino, Yoichi
Abstract : TaSb2, a candidate material for thermoelectric conversion, is studied to establish a method for the synthesis of polycrystalline bulk materials with a diameter greater than 10 mm. Polycrystalline TaSb2 materials with relative densities exceeding 97% are successfully prepared by combining the solid‐state reaction method with the spark plasma‐sintering process. The prepared TaSb2 sample is identified to be a semimetal with a pseudogap‐like electronic structure near the Fermi level using hard X‐ray photoelectron spectroscopy and band structure calculation. Abstract : A method for the synthesis of polycrystalline bulk materials of Weyl‐semimetallic TaSb2, a candidate for thermoelectric materials with a diameter of more than 10 mm, using solid‐state reaction and spark plasma sintering (SPS) processes, is established. The prepared TaSb2 sample is identified to be a semimetal with a pseudogap‐like electronic structure near the Fermi level using hard X‐ray photoelectron spectroscopy and band structure calculation.